Solving an Integral Equation by Using Fixed Point Approach in Fuzzy Bipolar Metric Spaces. (3rd December 2021) - Mani, Gunaseelan; Gnanaprakasam, Arul Joseph; Haq, Absar Ul; Jarad, Fahd; Baloch, Imran Abbas
Abstract : The purpose of this manuscript is to obtain some fixed point results under mild contractive conditions in fuzzy bipolar metric spaces. Our results generalize and extend many of the previous findings in the same approach. Moreover, two examples to support our theorems are obtained. Finally, to examine and strengthen the theoretical results, the existence and uniqueness of the solution to a nonlinear integral equation was studied as a kind of applications.